2019
DOI: 10.1186/s12955-019-1179-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial dental impact in adult orthodontic patients: what about health competence?

Abstract: Background Several studies have assessed the psychological benefits of orthodontic treatment; however, the impact of competence on psychological benefits remains unknown. Aims: To analyze the change of the perception of psychosocial dental impact in a sample of adults undergoing orthodontic treatment (mild/moderate dental malocclusions) and to assess the possible moderating effect of health competence level. Methods A longitudinal prospective design was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
3
8
0
2
Order By: Relevance
“…Their study suggests that psychological factors can also affect related oral health outcomes. Gonzalez et al [ 15 ] investigated the psychosocial aspects of orthodontics behaviors, and they suggested that individuals’ perceptions have a substantial influence on developing a positive change to oral health. These previous studies support that the perceptions of both medical providers and patients can affect the adoption of health-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Their study suggests that psychological factors can also affect related oral health outcomes. Gonzalez et al [ 15 ] investigated the psychosocial aspects of orthodontics behaviors, and they suggested that individuals’ perceptions have a substantial influence on developing a positive change to oral health. These previous studies support that the perceptions of both medical providers and patients can affect the adoption of health-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It should be studied in two different times – Before OT and After OT, ideally, including more stages – During OT and up to 10 years after OT. (6- 8, 14, 21 )…”
Section: Discussionmentioning
confidence: 99%
“…8 Although harms and complications related to orthodontic treatment are not life-threatening and less severe than other medical interventions, it is well reported that they might cause functional, social and psychological impairments to patients. 9 From an ethical point of view, orthodontists should be aware of all risks expected, and should inform their patients about them including those that are not under the control of the clinician, such as the disruptions of routine orthodontic follow-ups. In addition to adverse effects on patients’ treatment outcomes, disruptions in follow-ups can lead to financial burdens of the whole healthcare system providing any type of medical or dental care.…”
Section: Harms Related To Unsupervised Orthodontic Patientsmentioning
confidence: 99%